2013
DOI: 10.1002/jgrd.50236
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic activity signatures in wintertime stratosphere wind, temperature, and wave response

Abstract: [1] We analyzed ERA-40 and ERA Interim meteorological re-analysis data for signatures of geomagnetic activity in zonal mean zonal wind, temperature, and Eliassen-Palm flux in the Northern Hemisphere extended winter (November-March). We found that for high geomagnetic activity levels, the stratospheric polar vortex becomes stronger in late winter, with more planetary waves being refracted equatorward. The statistically significant signals first appear in December and continue until March, with poleward propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
140
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 47 publications
17
140
2
Order By: Relevance
“…The ozone losses lead to changes in the net radiative heating which change sign in late winter: a warming of the upper stratosphere at high latitudes dominates in mid-winters, while a cooling extending into mid-latitudes dominates in late winter and spring. Analysis of several decades of re-analysis data shows a warming of the mid to late winter upper stratosphere related to high geomagnetic activity (Lu et al, 2008;Seppälä et al, 2013) which is also reproduced in model experiments using free-running chemistry-climate models (Semeniuk et al, 2011;Baumgaertner et al, 2011). Based on older model experiments by Langematz et al (2005), Baumgaertner et al (2011) and Seppälä et al (2013) argue that the warming in the upper stratosphere and lower mesosphere is consistent with a direct radiative impact, while a cooling of the middle and lower stratosphere observed at the same time, during mid-winter (DJF in the Northern Hemisphere), is more likely the result of coupling between the vortex strength and wave propagation and reflection, an assumption strengthened by the apparent relation to the phase of the stratospheric quasi-biennial oscillation and the solar cycle (Lu et al, 2008;Seppälä et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ozone losses lead to changes in the net radiative heating which change sign in late winter: a warming of the upper stratosphere at high latitudes dominates in mid-winters, while a cooling extending into mid-latitudes dominates in late winter and spring. Analysis of several decades of re-analysis data shows a warming of the mid to late winter upper stratosphere related to high geomagnetic activity (Lu et al, 2008;Seppälä et al, 2013) which is also reproduced in model experiments using free-running chemistry-climate models (Semeniuk et al, 2011;Baumgaertner et al, 2011). Based on older model experiments by Langematz et al (2005), Baumgaertner et al (2011) and Seppälä et al (2013) argue that the warming in the upper stratosphere and lower mesosphere is consistent with a direct radiative impact, while a cooling of the middle and lower stratosphere observed at the same time, during mid-winter (DJF in the Northern Hemisphere), is more likely the result of coupling between the vortex strength and wave propagation and reflection, an assumption strengthened by the apparent relation to the phase of the stratospheric quasi-biennial oscillation and the solar cycle (Lu et al, 2008;Seppälä et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of observations using either geomagnetic activity or the hemispheric power index as proxies for particle precipitation suggest that such a coupling between EPP and atmospheric dynamics indeed exists during polar winter, characterized by a warming of the mid to late winter upper stratosphere at high latitudes (Lu et al, 2008;Seppälä et al, 2013). Analyses of several decades of surface air temperatures suggest that geomagnetic activity even affects tropospheric weather systems down to the surface in mid to late winter (Seppälä et al, 2009;Maliniemi et al, 2014).…”
mentioning
confidence: 99%
“…There are several publications (Lu et al, 2008;Seppälä et al, 2009Seppälä et al, , 2013, in which the authors investigated the geomagnetic activity effect in the atmosphere based on the meteorological measurements from the ERA-40 and ERAInterim data set. The authors studied the atmosphere climatology from 1000 to 1 hPa separately in the years with high and low geomagnetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…They found that high geomagnetic activity can drive a strengthening of the Northern Hemisphere polar vortex, with warming in the polar upper stratosphere and cooling below. Meteorological data analysis shows that the upper stratosphere warming starts in the beginning of December and lasts until March (Seppälä et al, 2013). The heating descends downwards during winter.…”
Section: Resultsmentioning
confidence: 99%
“…The recent review by Gray et al [2] classified solar forcing on the Earth's climate to be of four types: galactic cosmic rays, total solar irradiance (TSI), solar ultraviolet radiation (UV), and energetic particle precipitations (EPP). Although EPP has not attracted much attention compared with TSI and UV in the past, several recent studies indicate that EPP could have a significant impact on the Earth's climate, comparable with that of TSI and UV [3][4][5]. Seppälä and Clilverd ([6]; hereafter SC14) divided the past 54 boreal winters into solar maximum, solar minimum, and high energetic particle forcing (EPF) years based on the F10.7 radio flux and the Ap index.…”
mentioning
confidence: 99%